Induction Therapy and Stem Cell Mobilization in Patients with Newly Diagnosed Multiple Myeloma - Roberto Ria; Antonia Reale; Antonio Giovanni Solimando; Giuseppe Mangialardi; Michele Moschetta; Lucia Gelao; Giuseppe Iodice; Angelo Vacca (Stem Cells International)
Autologous stem cell transplantation (ASCT) is considered the standard therapy for younger patients with newly diagnosed symptomatic multiple myeloma (MM). The introduction into clinical practice of novel agents, such as the proteasome inhibitor bortezomib and the immunomodulatory derivatives (IMiDs) thalidomide and lenalidomide, has significantly contributed to major advances in MM therapy and prognosis. These novel agents are incorporated into induction regimens to enhance the depth of response before ASCT and further improve post-ASCT outcomes. Between January 2000 and November 2011, 65 patients with MM were transplanted in the Department of Biomedical Science and Clinical Oncology at the University of Bari. According to Durie-Salmon, 60 patients had stage III of disease and 5 stage II. Only 7 patients were in stage B (renal failure). Induction regimens that were administered in two or more cycles were VAD (vincristine, adriamycin, and dexamethasone), Thal-Dex (thalidomide, dexamethasone), Len-Dex (lenalidomide, dexamethasone), Vel-Dex (bortezomib, dexamethasone), VTD (bortezomib, thalidomide, and dexamethasone), and PAD (bortezomib, pegylated liposomal doxorubicin, and dexamethasone). In mobilization procedure, the patients received cyclophosphamide and granulocyte colony-stimulating factor (G-CSF). The number of cells collected through two or more leukapheresess, response after induction, and toxicity were evaluated to define the more adequate up-front induction regimen in transplantation-eligible MM patients.